Safety evaluation of a food enzyme with phospholipase A1 and lysophospholipase activities from the genetically modified Aspergillus niger strain PLN - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme with phospholipase A1 (phosphatidycholine 1‐acylhydrolase, EC 3.1.1.32) and lysophospholipase (2‐lysophosphatidylcholine acylhydrolase, EC 3.1.1.5) activities is produced with the genetically modified Aspergillus niger strain PLN by DSM. The genetic modifications do not give rise to safety concerns. The food enzyme is free from viable cells of the production organism and its DNA. It is intended to be used for the production of refined edible fats and oils by degumming. Since residual amounts of total organic solids are removed during this process, dietary exposure was not calculated and toxicological studies were considered unnecessary for the assessment of this food enzyme. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and no matches were found. The Panel considered that the risk of allergic reactions upon dietary exposure cannot be excluded, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.